Effectiveness, tolerability and safety of Direct Acting Antivirals in Mexican individuals with Hepatitis C virus genotype-1 and previous pegylated interferon and ribavirin therapy - Daniel Melendez-Mena; Miguel Angel Mendoza-Torres; Virginia Sedeño-Monge; Víctor Hugo García y García; Elain Rivera-García; Laura Sánchez-Reza; María del Carmen Baxin Domínguez; Belinda Guzmán-Flores; Ygnacio Martinez-Laguna; José Manuel Coronel Espinoza; Iván Galindo-Santiago; Juan Carlos Flores-Alonso; et al. (PeerJ, 2021)
Background Direct Acting Antivirals (DAAs) represent a large improvement in the treatment of chronic hepatitis C, resulting in <90% sustained virological response (SVR). There are no reports on the real-world DAA response for Mexico and few reports exist for Latin America. The aim of the study was to report SVR, and immediate benefits with the DAA treatments sofosbuvir, ledispavir, with/without ribavirin (SOF/LDV ± RBV) and ombitasvir, paritaprevir, ritonavir, dasabuvir with/without RBV (OBV/PTV/r/DSV ± RBV) in patients with viral genotype 1a or 1b, and who did not respond to previous peginterferon/ribavirin (PegIFNα2a+RBV) therapy. Methods A descriptive, ambispective, longitudinal study was conducted. A cohort of 261 adult patients received PegIFNα2a+RBV therapy before 2014; 167 (64%) did not respond, 83 of these were subsequently treated with SOF/LDV ± RBV or OBV/PTV/r/DSV ± RBV. Child-Pugh-Score (CPS), Fibrosis-4 (FIB-4), and AST to Platelet Ratio Index (APRI) were evaluated before and after treatment. Results SVR with PegIFNα2a+RBV was 36%, and 97.5% with DAAs. CPS, FIB-4 and APRI improved significantly after DAA treatment, mainly because of liver transaminase reduction. Conclusions DAA treatment showed excellent SVR rates in Mexican patients who had not responded to PegIFNα2a+RBV therapy. Improvement in CPS, FIB-4 and APRI without improvement in fibrosis was observed in cirrhotic and non-cirrhotic patients, as well as considerable reduction in liver transaminases, which suggests a reduction in hepatic necroinflammation.